CRIMINOLOGICAL STUDY OF CORRUPTION IN ABUSE OF POSITION AUTHORITY - Linda, Rosa; Prawira, A. Yudha (Faculty of Law Sriwijaya University, 2023)
In carrying out their duties and functions legally, officials have been regulated by law, but in exercising authority in office, they are also limited by law. Forms of abuse of power by public officials who commit corruption in a position and use it for personal and group interests to enrich themselves and certain groups and harm many people or the general public, namely in cases of corruption. Abuse of authority in office, namely in criminal acts of corruption by one of the university rectors in Lampung, followed by criminal acts of corruption in the Bengkalis Island Outer Ring Road improvement project and the Deputy Attorney General of the Manado State Attorney General’s Office. So, this needs to be studied in depth through criminological studies to determine the factors that cause someone to commit a crime. This study uses empirical normative research methods and statutory, conceptual, and case study approaches. The results of this study indicate that several factors influence an official who commits a criminal act of corruption. These internal factors include personality traits such as human greed, poor morals, and dishonesty. Next are external factors, including opportunity and economic factors (consumptive lifestyle). Efforts to deal with the criminal act of corruption and abuse of authority in the office can be carried out through preventive efforts, namely by building morale, honest attitude, and a clean work ethic. Then, through repressive efforts, severe penalties are imposed that create a deterrent effect and create fear for others to commit corruption.